Peminjaman dan Pengembalian Buku Perpustakaan Dengan Metode Rapid Application Development Pada SMA Nusantara 1 Tangerang - Noer Azni Septiani; Retno Wati (Infotek: Jurnal Informatika dan Teknologi, 2021)
In order to support national education through the provision of learning resources, the library must act as a learning center that meets the needs of students, especially at SMA Nusantara 1 Tangerang. Currently, the application of the system for borrowing and managing books to making reports at the SMA Nusantara 1 Tangerang library is still done manually, so errors can occur in recording and data recorded on paper that is damaged or lost at any time. This design program is made so that the process of borrowing and developing books to making library reports at SMA Nusantara 1 Tangerang can be carried out effectively and efficiently, the development of a system for borrowing and writing books at SMU Nusantara 1 Tangerang can be done effectively and efficiently, because it is one of the system methods aimed at providing much faster development and getting better quality results. The author uses RAD in addition to aiming to shorten the time usually required in the traditional system development life cycle between the design and implementation of an information system.